Depletion modeling of liquid dominated geothermal reservoirs - Olsen, G. (Stanford Geothermal Program (U.S.), 1984)
Depletion models for liquid-dominated geothermal reservoirs are derived and presented. The depletion models are divided into two categories: confined and unconfined. For both cases depletion models with no recharge (or influx), and depletion models including recharge, are used to match field data from the Svartsengi high temperature geothermal field in Iceland. The influx models included with the mass and energy balances are adopted from the petroleum engineering literature. The match to production data from Svartsengi is improved when influx was included. The Schilthuis steady-state influx gives a satisfactory match. The finite aquifer method of Fetkovitch, and the unsteady state method of Hurst gave reasonable answers, but not as good. The best match is obtained using Hurst simplified solution when lambda = 1.3 x 10{sup -4} msup -1. From the match the cross-sectional area of the aquifer was calculated as 3.6 kmsup 2. The drawdown was predicted using the Hurst simplified method, and compared with predicted drawdown from a boiling model and an empirical log-log model. A large difference between the models was obtained. The predicted drawdown using the Hurst simplified method falls between the other two. Injection has been considered by defining the net rate as being the production rate minus the injection rate. No thermal of transient effects were taken into account. Prediction using three different net rates shows that the pressure can be maintained using the Hurst simplified method if there is significant fluid reinjection. 32 refs., 44 figs., 2 tabs.